Study Of Reliability Of Smart Parking Systems Based On Microcontroller Esp 8266 NodeMcu - Adril Arnas; Solly Aryza; Hamdani (Sean Institute, 2021)
Automatic system is a process to control the operation of an a tool that can automatically replace the role of humans. One of the industries that is also experiencing rapid progress is in the field of parking (Smart Parking) for vehicles, both two-wheeled and four-wheeled vehicles. The current parking system still uses a lot of conventional parking systems that only utilize parking lots and parking attendants who control each incoming vehicle and also often do not pay attention to the capacity of the parking lot owned by a building. The research describes a design to build a parking prototype to make it easier for drivers to find empty parking slots. The tool that will be built will start when the car enters the parking area and is detected by the TCRT-5000 sensor, then the servo opens the gate at the command of the Arduino and the driver looks for an empty parking lot. The driver can see the empty parking slots through the parking application that is connected to the database through the Esp 8266 NodeMcu. The LCD will issue an output in the form of letters and numbers.